Pengaruh Latihan Passing Daerah Terhadap Peningkatan Hasil Passing Pendek Pada Permainan Futsal - Raka Muhammad Haque; Sri Maryati; Hendra Rustiawan; Risma Risma (Universitas Galuh, 2024)
The aim of the research proposed by the author is to determine whether there is a significant influence of regional passing training on improving short passing results in futsal games at Karangpucung State Vocational School. The research method used in this study is pre-experimental designs (nondesigns), one of the designs used in this study is one-group pretest-posttest design. The population in this study were 26 male students who participated in futsal extracurricular activities at SMK Negeri Karangpucung. The sample used was 26 people. Based on the results of the t-test calculation, the t-count value was obtained at 4.24. The t-count value is greater than the t-table value. The conclusion is that the null hypothesis is rejected and the working hypothesis is accepted, this indicates that there is a significant influence of the form of passing variation training on improving short passing results in futsal games at SMK Negeri Karangpucung.